Five new species of Metapolybia Ducke, 1905, with the description of the male genitalia of seven species of the genus (Hymenoptera, Vespidae, Polistinae) - Cortes, Gustavo B. [UNESP]; Noll, Fernando B. [UNESP]; Carpenter, James M.; Andena, Sergio R. (My University, 2024)
Five new species of Metapolybia are described, Metapolybia carpenteriana, Andena & Noll, sp. nov. (Ecuador, Peru), Metapolybia pseudodocilis Cortes, sp. nov. (Bolivia), Metapolybia richardsi Andena, sp. nov. (Ecuador), Metapolybia sulamerica Carpenter, sp. nov. (Colombia), Metapolybia zucchiana Andena & Carpenter, sp. nov. (Panama), in addition to the hitherto unknown males of M. bromelicola, M. encantata, M. mesoamerica, M. servilis and M. rufata plus two new species. Comparative remarks for the species are given.
Keywords: Epiponini; Paper wasps; Social wasps